STRATEGI MENGINTEGRASIKAN PENDIDIKAN KARAKTER DALAM KEHIDUPAN SEKOLAH - Syarwani Ahmad (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2017)
It stands to reason that character education should be integrated into all subjects. The reasons are that improving the noble character of the students is the responsibility of all teachers, all teachers must be a commanding example. The formation of a strong human resource character is necessary to face the tougher global challenges. Human resource character is formed through the process of formal education, non formal, and informal that all three must bersinergis. Character education means making a genuine, systematic and sustained effort to awaken and strengthen the awareness and confidence of all Indonesians that there will be no better future without building and strengthening the character of the Indonesian people. In other words, there is no better future that can be realized without honesty, without improving self-discipline, without persistence, without high learning spirit, without developing a sense of responsibility, without cultivating unity in the midst of diversity, without the spirit to contribute progress together, and without confidence and optimism.